The degree of practicing servant leadership among the principals of governmental secondary schools in Amman governorate and its relation to teachers’ motivation towards work - Abu Roman, Sana Abdullah Hussain (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the degree of practicing servant leadership by the principals of governmental secondary school in Amman governorate and its relation to teachers’ motivation towards work, from teachers’ point of view, Descriptive correlative research method as the most suitable method for this study and adopted the questionnaire as a means of collecting data both for the servant leadership or motivation. The sample of the study consisted of (347) teachers. They were chosen intentionally from governmental secondary schools in Amman. The descriptive correlational methodology was used. Two questionnaires were used as a tool of the study to collect data, after finding their validity and reliability; the findings showed that the degree of practicing servant leadership by governmental secondary school principals in Amman governorate from teachers’ point of view was low. The level of teachers’ motivation towards work was low too. There was a positive significant correlational relationship at (α≤0.05) between the degree of practicing servant leadership by governmental secondary school principals in Amman governorate and teachers’ motivation towards work. The Pearson value was (0.61). The main recommendations of the study: organizing training courses on servant leadership for principals of public secondary schools in Jordan., and the adoption of servant leadership in the evaluation process and the selection of school principals by the Ministry of Education.